Partial Likelihood-Based Scoring Rules for Evaluating Density Forecasts in Tails - Cees Diks; Valentyn Panchenko; Dick van Dijk (Tinbergen Institute, 2008)
We propose new scoring rules based on partial likelihood for assessing the relative out-of-sample predictive accuracy of competing density forecasts over a specific region of interest, such as the left tail in financial risk management. By construction, existing scoring rules based on weighted likelihood or censored normal likelihood favor density forecasts with more probability mass in the given region, rendering predictive accuracy tests biased towards such densities. Our novel partial likelihood-based scoring rules do not suffer from this problem, as illustrated by means of Monte Carlo simulations and an empirical application to daily S&P 500 index returns.
Keywords: C12; C22; C52; C53; 330; density forecast evaluation; scoring rules; weighted likelihood ratio scores; partial likelihood; risk management; Statistische Verteilung; Qualitatives Verfahren; Zeitreihenanalyse; Schätztheorie; Schätzung; USA